The Stereochemistry of the 1,4-Elimination of Thiocyanic Acid from Hex-3-ene-2,5-diyl Dithiocyanates - Schoepfer, Joseph; Eichenberger, Eugen; Neier, Reinhard (My University, 1993)
The elimination of thiocyanic acid from the stereoisomers of the hex-3-ene-2,5-diyl dithiocyanates, 4a, 4b, 6a and 6b, in the presence of a strong neutral base in an organic solvent, yields mixtures of the hex-2,4-dien-2-yl thiocyanates 9, 10 and 11via a preferentially syn process.